CAGW and TAT‐NLS peptides functionalized multitargeting gene delivery system with high transfection efficiency. (13th June 2019) - Duo, Xinghong; Bai, Lingchuang; Wang, Jun; Ji, Hao; Guo, Jintang; Ren, Xiangkui; Shi, Changcan; Xia, Shihai; Zhang, Wencheng; Feng, Yakai
Abstract : Gene therapy has attracted much attention in vascular tissue engineering. However, it is still challenging to develop a novel gene carrier with multifunction to overcome the barriers in gene delivery. Herein, the multitargeting gene complexes were developed based on methoxy‐poly(ethylene glycol)‐b‐poly‐(D, L‐lactide‐co‐glycolide) (mPEG‐b‐PLGA), poly(d, l ‐lactide‐co‐glycolide)‐g‐polyethylenimine‐g‐CAGW (PLGA‐g‐PEI‐g‐CAGW), cell‐penetrating peptide YGRKKRRQRRR (TAT), nuclear localization signals (NLS), and pEGFP‐ZNF580 (pDNA) with the purpose of enhancing the transfection of endothelial cells (ECs). The low cytotoxic multitargeting gene complexes could be easily prepared by adjusting the weight ratio of mPEG‐b‐PLGA and PLGA‐g‐PEI‐g‐CAGW. Meanwhile, CAGW peptide with selectively ECs‐targeting ability and TAT‐NLS peptide sequence with both cell‐penetrating ability and nuclear targeting capacity were simultaneously introduced into gene complexes in order to enable them with the multitargeting function so as to improve their gene delivery capacity. The pDNA loading capacity of these gene complexes was confirmed by agarose gel electrophoresis assay. MTT results demonstrated that the relatively cell viability of the multitargeting gene complexes was higher than those of other groups. These multitargeting gene complexes showed higher internalization and transfection efficiencies than other groups. These results revealed that CAGW and TAT‐NLS peptide sequences benefited for efficient gene delivery. Furthermore, the wound healing assay demonstrated that the multitargeting gene complexes could promote the proliferation and migration of ECs. These results collectively demonstrated that CAGW and TAT‐NLS peptides functionalized gene delivery system could effectively enhance the transfection of ECs, which has great potential in vascular tissue engineering.